Assessing Human Molybdenum Nutritional Status by Analyzing Frequency distribution Properties in the Hair and Whole Blood with a Median Derivatives Bioassay. (29th May 2020) - Momčilović, Berislav; Prejac, Juraj; Mimica, Ninoslav
Abstract: Objectives: Molybdenum is the essential trace element in human nutrition since it is a part of a pterin coenzyme which is essential for the activity of various oxidases. High doses of Mo are neurotoxic to the human brain. The safe adequate intake of Mo is set at 75–200 µg·g −1, but there is no available long-term biological indicator tissue to assess the Mo nutritional status. The aim of this study was to assess human Mo nutritional status with a median derivatives bioassay. Methods: We analyzed frequency distribution of hair Mo ( H Mo) in a prospective, observational, cross sectional and exploratory epidemiological study of 1073 apparently healthy adults (339 men, M and 734 women, W) from Zagreb, CROATIA. Whole blood Mo ( WB Mo) was assessed in a population subsample of 143 W and 91 M. Both hair and whole blood, a long- and short-term biological indicator, respectively were analyzed for Mo with the ICP MS at the Center for Biotic Medicine, Moscow, Russia: an ISO certified bioelement (electrolytes, trace- and ultra-trace elements) analytical laboratory. Hair Mo natural frequency distribution was analyzed with the aid of median derivatives bioassay logistic sigmoid curve for men and women separately. The range of values below the linear segment of the sigmoid curve (the adequate Mo intake) was considered to reflect Mo deficiency, whereas the values above that linear range indicate Mo dietary excess. The adequate linear range may be further subdivided into marginal (subclinical), true adequate, and ample region with a 30:60:10 ratio, respectively. Results: The linear segment of the hair Mo deposition was distinctly different (ng·g −1 ) and higher in M (34–75) than W (27–57) with the observed median ♀/♂ ratio 0.82. The marginal (subclinical) interval ranges are M 34–46.3, W 27–36). However, there were no difference in the WB Mo confidence intervals between M (455–1380) and W (480–1145); the Median ♀/♂ observed ratio is 0.93. Conclusions: Adequate human population Mo nutritional status may be accurately assessed by analyzing hair Mo frequency distribution with the median derivatives bioassay. Apparently, there is gender dependent delay of Mo hair saturation in the men hair. For the first time it was possible to differentiate the subclinical levels of sparsely adequate dietary Mo. Funding Sources: Institute for Research and Development of Sustainable Eco Systems, 10, 000 Zagreb, Croatia.